A WEF nexus–based planning framework to assess progress towards Sustainable Development Goals - Mpandeli, S.; Nhamo, L.; Liphadzi, S.; Molwantwa, J.; Mabhaudhi, Tafadzwanashe (CRC Press, 2024)
The water-energy-food (WEF) nexus has transitioned into an important transformative approach for understanding the intricate interlinkages between global resource systems on which humankind depends to achieve and sustain various social, economic, and environmental goals. This chapter discusses a WEF nexus–based framework developed to facilitate this understanding and guide the progress towards Sustainable Development Goals (SDGs) assessment. Understanding the intricate interlinkages among the WEF resources and the progress towards SDGs is critical for achieving a sustainable and resource-secure future. Since the introduction of the SDGs, the WEF nexus has evolved into an important theoretical, analytical, and conceptual framework for understanding and systematically analysing the intricate socio-ecological interactions and their impact on human health. This has seen the approach becoming a useful decision-support tool for improved spatio-temporal and cross-sectoral coordination, management, and use of natural resources. This has facilitated identifying and managing trade-offs and synergies through informed developmental interventions that allow for more integrated and cost-effective planning, decision-making, implementation, monitoring, and evaluation. The chapter provides the methodological pathways to strategic policy decisions towards resilience, adaptation and sustainable development.